2017
DOI: 10.1002/chem.201701986
|View full text |Cite
|
Sign up to set email alerts
|

Nonheme Iron‐Oxo‐Catalyzed Methane Formation from Methyl Thioethers: Scope, Mechanism, and Relevance for Natural Systems

Abstract: A range of nonheme oxo-iron(IV) model systems with tetra- or pentadentate ligands is shown to produce methane from methionine and other thioethers. This model reaction for the natural aerobic production of methane is shown to proceed via two sulfoxidation steps involving the oxo-iron(IV) complexes, with a bifurcation in the second step that either produces the sulfone or leads to demethylation with similar probabilities. In the presence of O , the resulting methyl radicals produce methanol and formate or, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 74 publications
2
52
1
Order By: Relevance
“…Unfortunately, δ 13 C-DIC and δ 13 C-POC values could not be determined in our set of experiments to allow for more detailed calculations. However, our results clearly indicate that hydrogen carbonate is the principal inorganic carbon precursor of 13 CH 4 produced in algae, but intermediate metabolites are likely to be formed from which CH 4 is released, possibly by cleavage of sulfurbonded methyl groups of methyl thioethers and sulfoxides (Althoff et al, 2014;Lenhart et al, 2016;Benzing et al, 2017).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Unfortunately, δ 13 C-DIC and δ 13 C-POC values could not be determined in our set of experiments to allow for more detailed calculations. However, our results clearly indicate that hydrogen carbonate is the principal inorganic carbon precursor of 13 CH 4 produced in algae, but intermediate metabolites are likely to be formed from which CH 4 is released, possibly by cleavage of sulfurbonded methyl groups of methyl thioethers and sulfoxides (Althoff et al, 2014;Lenhart et al, 2016;Benzing et al, 2017).…”
Section: Discussionmentioning
confidence: 68%
“…The CH 4 formation from thioethers (MET, DMS) and their corresponding sulfoxides (MSO, DMSO) might be catalyzed by nonheme iron-oxo (IV), thus forming methyl radicals ( q CH 3 ) from homolytically broken sulfur methyl bounds (R-CH 3 ), leading to CH 4 under oxidative conditions (Althoff et al, 2014;Benzing et al, 2017). The tested compounds are found in high cellular concentrations in E. huxleyi, Chrysochromulina sp., and P. globosa, and nonheme iron-oxo (IV) has been identified as an active intermediate in the catalytic cycles of a number of biological enzymatic systems (Hohenberger et al, 2012).…”
Section: Potential Mechanism Of Ch 4 Formation From Thioethersmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the stable isotope labeling approach should be considered as a proof of concept, showing that methyl groups of all tested substance serve as precursor compounds of CH4. Althoff et al (2014) and Benzing et al (2017) suggested a chemical reaction of DMSO, DMS and MSO that leads to CH4 formation in eukaryotes, especially, in marine algae containing elevated concentration of these compounds. We have therefore tested whether the methyl groups of these substances can actually be converted to CH4 in marine algae cultures.…”
Section: Interactive Commentmentioning
confidence: 99%